Planning education through Theory of Change: when pedagogical thought meets methodology - Sartori, Valentina (Form@re - Open Journal per la formazione in rete, 2025)
Theory of Change (ToC) is a well-known planning methodology, adopted more or less explicitly by various nonprofit and charitable organizations willing to pursue relevant change, as well as targets of long-term social impact. A close look to the technical characteristics of this participatory and process-centered tool suggests various similarities with educational goals and strategies specifically related to pedagogical thought, thus proving itself an extremely fruitful method of educational planning. Progettare educazione con la Teoria del Cambiamento: quando la riflessione pedagogica incontra la metodologia. La Teoria del Cambiamento (ToC) è una metodologia di progettazione ben nota, adottata più o meno esplicitamente da diverse organizzazioni non profit e filantropiche desiderose di perseguire cambiamenti rilevanti, così come obiettivi di lungo periodo di impatto sociale. Osservando da vicino le caratteristiche di questo strumento partecipativo e centrato sul processo, si notano svariate similarità con le intenzioni educative e le strategie specificamente correlate al pensiero pedagogico, mostrando così di essere un metodo estremamente fruttuoso di progettazione educativa.